2008 DoD HPCMP Users Group Conference 2008
DOI: 10.1109/dod.hpcmp.ugc.2008.65
|View full text |Cite
|
Sign up to set email alerts
|

Free-Surface Proximity Effects in Developed and Super-Cavitation

Abstract: This paper summarizes a number of large-scale multiphase computation fluid dynamics (CFD) analyses of relevance to the Defense Advanced Research Projects Agency (DARPA) Underwater Express Program. The specific focus of this paper is on developed and supercavitating configurations related to submerged vehicles and control surfaces where proximity to the free-surface is relevant. The results and interpretation of several large scale simulations, enabled by adaptive and overset meshing technology, Large Eddy Simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Their results show that for angle of attacks bellow the stall condition, 2D and 3D results agrees suitably for the lift coefficient, general cavity development, stability, and cavity size. They showed that surface pressure distributions of the 2D case are consistent with the three dimensional predictions, especially away from the tip [37]. Qin et al [40,41] and Arndt [42] considered 2D LES simulation of cavitating flow over hydrofoil and physical results were obtained for classification of vortex shedding mechanism in sheet/cloud cavitation regimes.…”
Section: A Note On 2d Les Simulationmentioning
confidence: 57%
See 2 more Smart Citations
“…Their results show that for angle of attacks bellow the stall condition, 2D and 3D results agrees suitably for the lift coefficient, general cavity development, stability, and cavity size. They showed that surface pressure distributions of the 2D case are consistent with the three dimensional predictions, especially away from the tip [37]. Qin et al [40,41] and Arndt [42] considered 2D LES simulation of cavitating flow over hydrofoil and physical results were obtained for classification of vortex shedding mechanism in sheet/cloud cavitation regimes.…”
Section: A Note On 2d Les Simulationmentioning
confidence: 57%
“…The key reason for employing 2D LES in the current work is the large computational cost of 3D LES simulation. 3D LES simulation typically needs large computational resources [37][38][39]. Therefore, like some other researches, i.e., Refs.…”
Section: A Note On 2d Les Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no additional dissipation for the central difference format, so it is well suited for LES to discretize the diffusion flux. The main reason for 2D LES was chosen in this paper instead of 3D LES is that the large computing resources were required in 3D simulation [54][55][56]. Many other researchers [55,[57][58][59] have also conducted many studies based on 2D LES, and the accuracy of 2D LES had also been reported in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…In this case the body will suffer only half drag when the cavitation number is near zero [9]. Using computationally supercavitating flow, Owis et al considered the compressibility of supercavitating flow and improved a numerical method for both single and multi-phase flows [10][11][12]. Drag force for NACA66 foil and a flat plate was investigated by Seif and the CFD model was successfully tested [13].…”
Section: Introductionmentioning
confidence: 99%